A GUIDELINE TO ENCOURAGE LEARNING LOSS RECOVERY BASE ON THE FOUR IDDHIPADA OF SCHOOLS CLUSTER IN PHRUPHI-KHUANSRI UNDER SURATTHANI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Treephan, Nattida; PhrakhruPhichitsupakarn; Yotharak, Maliwan (Journal of Educational Review Faculty of Education in MCU, 2025)
The objectives of this research article were: 1) to study the condition of learning loss recovery, 2) to study the strategies for promoting remedial learning loss recovery measures based on the Four Iddhipad, 3) to propose strategies for promoting remedial learning loss recovery measures based on the Four Iddhipad in the Phruphi-Khuansri network schools under the Surat Thani Primary Educational Service Area Office 3. This was qualitative research. The data were collected by in-depth interviews with 15 key informants, 5 experts and focus group by 7 qualified persons. The qualitative data were analyzed using content analysis and thematic analysis, followed by descriptive writing. The results of the study were as follows: 1) The condition of learning loss recovery, founded that educational institutions had adjusted their curricula to accommodate students that learning loss. However, teachers had not received sufficient training, leading to misunderstandings. The lack of collaboration from all sectors had hindered access to external learning resources. Additionally, there was an absence of a modern data management system. The students were not engaging in learning activities, and there were still discrepancies in resource accessibility. These factors had hindered both educators and students from continuously developing their skills. 2) The study of strategies to promote learning loss recovery measures based on the Four Iddhipad principles, identified 7 essential measures for recovering from learning loss: (1) Designing a new learning management process to respond to changing contexts and student needs. (2) Empowering the development of teachers and school administrators. (3) Fostering effective collaboration in learning management among schools, teachers, parents, communities, and all relevant sectors. (4) Developing a digital library for open learning and integrating educational information systems. (5) Cultivating a positive attitude towards learning and promoting students’ well-being, Both physically and mentally. (6) Enhancing learning management through systematic and effective use of technology. (7) Providing welfare, ensuring safety, and boosting morale. These measures were aligned with the Four Iddhipad, which included: (1) Chanda (Satisfaction), (2) Viriya (Effort), (3) Citta (Concentration), (4) Vimas (Reflection). 3) The presentation of guidelines for promoting revival measures for learning loss based on the Four Iddhipad principles were found to be appropriate, feasible, and beneficial. It could be implemented in practice.